In silico screening of cucurbitacin variants identifies 11-deoxycucurbitacin I as a candidate ligand for the NACHT domain of NLRP3 - Sarmoko; Ahmad Zammi Autadan Hakim; Nisa Yulianti Suprahman; Refsya Azanti Putri; Muhammad Yogi Saputra; Tantri Liris Nareswari; Manami Toriyama (Pharmacy Reports, 2026)
Chronic inflammation contributes to a wide range of diseases, driving the need for novel anti-inflammatory agents with minimal side effects. The NACHT domain of NLRP3 mediates ATP-dependent inflammasome assembly and represents a validated target for anti-inflammatory therapy. This study aimed to predict and compare the binding interactions of twenty-two cucurbitacin variants against the NACHT domain using molecular docking, following geometry optimization with Density Functional Theory (B3LYP/6-31G(d)). Docking validation reproduced the native ligand pose with an RMSD of 0.87 angstrom. Among all variants tested, 11-deoxycucurbitacin I showed the most favorable predicted binding energy (-7.38 kcal/mol), sharing several interacting residues with the native ligand RM5, including Ala227, Ala228, Pro352, Ile411, Phe575, and Met661, although its predicted affinity remained weaker than that of RM5 (-10.35 kcal/mol). These shared contacts suggest that 11-deoxycucurbitacin I may engage a similar region of the NACHT inhibitor-binding pocket as RM5. In conclusion, 11-deoxycucurbitacin I is identified as the most favorable predicted binder among the cucurbitacin variants tested toward the NACHT domain, representing a candidate warranting further experimental validation.